Language Dominance and Cognitive Flexibility in French–English Bilingual Children - Nicoladis, Elena; Hui, Dorothea; Wiebe, Sandra A. (Frontiers in Psychology, 2018)
Some studies have reported a cognitive advantage for bilingual children over monolinguals and other studies have not. One possible reason for these conflicting results is that the degree of cognitive flexibility is related to individual differences in language dominance and use. More balanced bilinguals who separate their languages by context might have to learn to reduce inter-language interference and therefore show greater cognitive flexibility. The goal of the present study was to test if language dominance is related to French-English bilingual children’s cognitive flexibility, using three different measures of language dominance: 1) parental reports of dominance, 2) relative scores on vocabulary tests, and 3) knowledge of translation equivalents. We also included two measures of language use: 1) living in a bilingual community (Montreal) or a monolingual community (Edmonton) and 2) language separation. Sixty-two French-English bilingual between 46 and 85 months of age participated. Children’s cognitive flexibility was assessed using the Advanced Dimensional Change Card Sort task. Children’s language knowledge and use was assessed in both French and English using a battery of tests. The results showed that none of the measures of language dominance or language use predicted cognitive flexibility. These results are inconsistent with the claim that individual differences in language dominance and use predict bilinguals’ executive functions.